Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Nilai-Nilai Keagamaan Islam - Sriyadi (Fakultas Agama Islam, 2014)
Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Nilai-Nilai Keagamaan Islam